Common Immune-Related Adverse Events of Immune Checkpoint Inhibitors in the Gastrointestinal System: A Study Based on the US Food and Drug Administration Adverse Event Reporting System - Bai, Xiaoyin; Jiang, Shiyu; Zhou, Yangzhong; Zhen, Hongnan; Ji, Junyi; Li, Yi; Ruan, Gechong; Yang, Yang; Shen, Kaini; Wang, Luo; Li, Guanqiao; Yang, Hong (Frontiers in Pharmacology, 2021)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment; however, immune-related adverse events (irAEs) in the gastrointestinal (GI) system commonly occur. In this study, data were obtained from the US Food and Drug Administration adverse event reporting system between July 2014 and December 2020. Colitis, hepatobiliary disorders, and pancreatitis were identified as irAEs in our study. Reporting odds ratio (ROR) with information components (IC) was adopted for disproportionate analysis. A total of 70,330 adverse events were reported during the selected period, 4,075 records of which were associated with ICIs. GI toxicities have been reportedly increased with ICI, with ROR025 of 17.2, 6.7, and 2.3 for colitis, hepatobiliary disorders, and pancreatitis, respectively. The risks of colitis, hepatobiliary disorders, and pancreatitis were higher with anti-CTLA-4 treatment than that with anti-PD-1 (ROR025 2.6, 1.3, and 1.1, respectively) or anti-PD-L1 treatment (ROR025 4.8, 1.3, and 1.3, respectively). Logistic analysis indicated that hepatobiliary disorders and pancreatitis more frequently occurred in female patients (adjusted odds ratio, 1.16 and 1.52; both p < 0.05). Consistently, polytherapy was a strong risk factor for colitis (adjusted odds ratio 2.52, p < 0.001), hepatobiliary disorders (adjusted odds ratio 2.50, p < 0.001), and pancreatitis (adjusted odds ratio 2.29, p < 0.001) according to multivariate logistic analysis. This pharmacovigilance analysis demonstrated an increased risk of all three GI irAEs associated with ICI therapies. The comparative analysis offered supportive insights on selecting GI irAEs for patients treated with ICIs.